In-plane magnetic field dependence of intrinsic Josephson junctions in Tl-Ba-Ca-Cu-O thin films - Warburton, P; Chana, O; Kuzhakhmetov, A; Hyland, D; Dew-Hughes, D; Grovenor, C; Koval, Y; Muller, P (2001)
We have fabricated intrinsic Josephson bridges using Tl-Ba-Ca-Cu-O thin films grown on vicinal lanthanum aluminate substrates, Measurements of the lock-in transition allow us align a magnetic field of up to 4T with the copper oxide planes to better than 0.3 degrees. This allows us to study the dynamics of Josephson fluxons in the films, For fields above 1.4T and at low currents we observe Josephson flux creep. Above a field-dependent threshold current we observe free flow of the fluxons with a flux-flow resistance which is proportional to field. The fluxons reach a field-independent velocity before the jump to the quasiparticle branch occurs. Our results suggest that the development of a sub-mm-wave oscillator using these bridges will require sub-micron patterning.